Lara Croft, tomb raider : a novelization - Odom, Mel. (New York : Pocket Books, 2001)
Lara Croft tries to prevent the Illuminati from using the All Seeing Eye to rule the world.
"A Minstrel book.".
"Based on the screenplay written by Patrick Massett & John Zinman and Simon West.".
Keywords: Adventure and adventurers -- Fiction; Antiquities -- Fiction